2016
DOI: 10.1017/jfm.2016.297
|View full text |Cite
|
Sign up to set email alerts
|

Instability and low-frequency unsteadiness in a shock-induced laminar separation bubble

Abstract: Three-dimensional direct numerical simulations (DNS) of a shock-induced laminar separation bubble are carried out to investigate the flow instability and origin of any low-frequency unsteadiness. A laminar boundary layer interacting with an oblique shock wave at $M=1.5$ is forced at the inlet with a pair of monochromatic oblique unstable modes, selected according to local linear stability theory (LST) performed within the separation bubble. Linear stability analysis is applied to cases with marginal and large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
6
24
0
Order By: Relevance
“…In this study the medium frequency dynamics is linked to the shedding of vortical structures at the end of the mixing layer. The high frequency dynamics S t ≈ 1-2 is also observed by Sansica et al (2016) who suggest that it is due to the transition process close to the reattachment point.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…In this study the medium frequency dynamics is linked to the shedding of vortical structures at the end of the mixing layer. The high frequency dynamics S t ≈ 1-2 is also observed by Sansica et al (2016) who suggest that it is due to the transition process close to the reattachment point.…”
Section: Introductionsupporting
confidence: 64%
“…Sansica et al (2014) carried out a DNS analysis of a two-dimensional (2-D) interaction at M = 1.5 forced either upstream of the separation, inside the circulation bubble or both, and found this low frequency unsteadiness to be particularly strong near the separation point and present even in the absence of an upstream forcing, indicating that incoming perturbations are not necessary to promote the low frequency unsteadiness in this type of interaction. Sansica, Sandham & Hu (2016) further showed that the flow in the interaction is convectively unstable due to oblique mode growth (on this subject, see also the work of Chang & Malik (1994)) and that the bubble acts like a filter-amplifier of low frequency disturbances at approximately S t ∼ 0.1. A broad band spectrum of low frequency fluctuations is localized in the vicinity of the separation point, around a Strouhal number of S t = 0.04, similarly to the turbulent case of Pirozzoli & Grasso (2006) mentioned above.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This model was later verified experimentally by Poggie & Smits (2001) and more recently derived analytically with supporting assumptions validated through LES by Touber & Sandham (2011). Sansica, Sandham & Hu (2016) also reproduced many of the key features of the oscillation by suitably forcing a laminar SBLI, showing that broadband low-frequency upstream content is not necessary to elicit a low-frequency response at the separation point. Rather the response can result from 'forcing' via transition downstream, which is then low-pass filtered by the interaction.…”
Section: Dynamic Linear Responsementioning
confidence: 62%